2018
DOI: 10.1002/chem.201800744
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Diarylmethyl Sulfones by Palladium‐Catalyzed Enantioselective Benzylic Substitution: A Remarkable Effect of Water

Abstract: A Pd/(R)-BINAP-catalyzed enantioselective benzylic sulfonation of diarylmethyl carbonates with sodium sulfinates proceeds to deliver the corresponding chiral diarylmethyl sulfones in good yields with high enantioselectivity. The reaction occurs in a dynamic kinetic asymmetric transformation (DYKAT) manner and thus provides convergent access to optically active benzylic sulfones from racemic secondary benzylic carbonates. Additionally, the addition of H O is found to be critical for high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The reaction proceeded in a dynamic kinetic asymmetric transformation (DYKAT) manner to form the enantiomerically enriched benzylic sulfones ( Scheme 260 ). 368 As the authors observed, the addition of H 2 O was found to be critical for high enantioselectivity. Several secondary benzylic carbonates with sodium benzenesulfinate delivered the corresponding chiral diarylmethyl sulfones in good yields with high enantioselectivity.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 95%
“…The reaction proceeded in a dynamic kinetic asymmetric transformation (DYKAT) manner to form the enantiomerically enriched benzylic sulfones ( Scheme 260 ). 368 As the authors observed, the addition of H 2 O was found to be critical for high enantioselectivity. Several secondary benzylic carbonates with sodium benzenesulfinate delivered the corresponding chiral diarylmethyl sulfones in good yields with high enantioselectivity.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 95%
“…In 2018, Miura et al described an asymmetric benzylic substitution of diarylmethyl carbonates with sodium sulfinates (Scheme 19). 37 The enantioselectivity was very low or almost absent under anhydrous conditions or with other proton sources. Only water had a positive impact on enantioselectivity, and up to 98% ee could be obtained under optimized conditions.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…On the other hand, our research group recently developed the palladium-catalyzed benzylic substitution of readily accessible and easy-to-handle diarylmethyl carbonates with carbon, nitrogen, oxygen, and sulfur nucleophiles . Additionally, the asymmetric version was also realized by the judicious choice of chiral bisphosphine ligands.…”
mentioning
confidence: 99%